When death was postponed: The effect of HIV medication on work and marriage - Mette Ejrnæs; Esteban García-Miralles; Mette Gørtz; Petter Lundborg (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
Over the last century, global life expectancy has increased tremendously. A longer planning horizon may change individuals' incentives to work, save, and marry but it has proven challenging to disentangle such incentive effects from those of improved health. In this paper, we study how individuals diagnosed with HIV reacted to the introduction of HIV medicine in 1995, which dramatically increased their life expectancy. To isolate the incentive effect, we use Danish register data on HIV-infected individuals and compare how outcomes evolved for individuals who were diagnosed before and after the medicine was introduced, but whose health had not yet been affected by their HIV diagnosis. Our results show that increases in the life expectancy of HIV-infected individuals greatly reduced the negative effect of receiving a HIV diagnosis on labor supply and earnings but did not affect important financial decisions, despite a much longer investment horizon. An increased life expectancy also affected marital behavior, where those facing a longer life expectancy where less likely to marry or cohabit after receiving a HIV diagnosis. Our results highlight that life expectancy gains from medical innovations impact individuals' incentives to work and marry, even when their underlying health is unchanged.
Keywords: D84; I12; J12; J21; 330; Life Expectancy; Labor Supply; Marriage; HIV